Participatory decision-making: The core of multi-stakeholder collaboration - Kaner, S.; Watts, J.; Frison, Emile A. (2008)
The purpose of this brief is to provide insights and guiding principles that can inspire readers to conduct multistakeholder collaboration more effectively. The objectives are to demystify the process of collaboration, to make its assumptions more accessible, and especially to encourage readers to adapt participatory values and practices to their own settings. The brief describes several time-tested tools and procedures that can be implemented in a straightforward manner.